Pengaruh Model Pembelajaran Problem Solving dengan Pendekatan STEM terhadap Kemampuan Pemecahan Masalah dan Hasil Belajar Biologi Siswa SMA - Annisa Maulida (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
In the 21st century,the world of education is experiencing strong competition that demands the ability of the younger generation in various fields such as science, technology, mathematics, responsibility and cooperation in facing the challenges of life in the future. Problem solving skills are considered important to prepare the next generation who are ready to compete and able to solve problems. The level of problem solving skills in Indonesia is still relatively low. This is because students find it difficult to understand the content of learning materials, especially biology, which has an impact on student learning outcomes. The ability to solve problems can be improved by using the STEM approach. Therefore a learning model that can improve problem solving skills and student learning outcomes is needed. This study used a Problem Solving learning model with STEM approach. The purpose of this study was to determine the effect of the Problem Solving learning model with a STEM approach that could improve the problem solving ability and learning outcomes of high school biology students. The research method. Learning activities in the control class were carried out using the STAD type cooperative learning model while learning in the experimental class used the Problem Solving learning model with a STEM approach. Student’s problem skills were measured using the Independent sample t-Test. Meanwhile, student’s biology learning outcomes were measured using ANOVA statistic test. The result of this study is problem solving ability data sig <0.05. Based on the results of data analysis, it could be concluded that Problem Solving learning models with a STEM approach affected the problem solving ability and learning outcomes of high school biology students
Entry oleh Arif 2026 Maret 05
Keywords: Problem Solving; STEM; Problem Solving Skills; Learning Outcomes.